A new species of Syncalypta from South Africa.: (12th contribution to Coleoptera Byrrhidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
After some preliminary remarks on the subfamily Syncalyptinae, on its genera and their distribution, the species certainly belonging to Syncalypta are reviewed and a new species is described: S. russelli from South Africa. This is the first Syncalyptinae recorded in the Ethiopian Region (Transvaal, Rivonia near Johannesburg, 9-XI-1968) where it has been collected by M. I. Russell.